2012
DOI: 10.2147/tcrm.s26673
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in a sample of the 6- to 16-year-old overweight or obese pediatric population: a comparison of two definitions

Abstract: PurposeThe purpose of this study was to estimate the presence of metabolic syndrome (MS) in a group of children and adolescents with a body mass index (BMI) above the 85th percentile for their age and sex in Qazvin Province, Iran; to evaluate the relationship between obesity and metabolic abnormalities; and to compare two proposed definitions of MS.Patients and methodsThe study was conducted on 100 healthy subjects aged between 6 and 16 years (average age, 10.52 ± 2.51 years) with a high BMI for their age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
(84 reference statements)
3
14
1
4
Order By: Relevance
“…The analysis of anthropometric variables according to weight status has confirmed that each component of the MetS worsens with increasing weight, independent of sex (27). As has been reported previously (26,28,29) and was found in our study, several parameters did not show significant differences between overweight and obese children, except for a significantly higher WC in the obese group, which reinforces its importance as a risk indicator. The impaired levels of insulin, HOMA-IR, TG, HDL-C, and total-and HMW-adiponectin in the obese group compared to the normal group confirm the remarkable impact of obesity on metabolic disorders.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of anthropometric variables according to weight status has confirmed that each component of the MetS worsens with increasing weight, independent of sex (27). As has been reported previously (26,28,29) and was found in our study, several parameters did not show significant differences between overweight and obese children, except for a significantly higher WC in the obese group, which reinforces its importance as a risk indicator. The impaired levels of insulin, HOMA-IR, TG, HDL-C, and total-and HMW-adiponectin in the obese group compared to the normal group confirm the remarkable impact of obesity on metabolic disorders.…”
Section: Discussionsupporting
confidence: 90%
“…A identificação precoce da SM em crianças e adolescentes é importante, a fim de evitar a morbi-mortalidade que geralmente é causada por esta síndrome. Contudo, a avaliação dos fatores de risco para SM exige valores apropriados para diferentes idades e sexos (Saffari, Jalilolghadr, Esmailzadehha, & Azinfar, 2012) e, dessa forma, necessita definição padronizada e internacionalmente aceita para seu diagnóstico, pois as prevalências de SM em crianças e adolescentes variam não só por causa de diferentes populações estudadas, como também pela adoção de definições diferentes (Andaki, Tinoco, Mendes, & Amorim, 2012).…”
Section: Discussionunclassified
“…The increasing incidenceof childhood obesity and the earlier onset of insulinresistance, hypertension, and dyslipidemia increased risk factors forcardiovascular disease. These metabolic abnormalities in children may predict that diabetesand cardiovascular disease complications may appear earlier than previously thought [3,4]. The pathogenesis of obesity-related insulin resistance and type 2 diabetes involve chronic low-grade inflammation and production of inflammatory cytokinescontributing tovascular reactivity,endothelial dysfunctionanddiabetic vascular complications [5].…”
Section: Introductionmentioning
confidence: 97%
“…Its prevalence has increased so significantly in recent years that many consider it a major health concern of the developed world [1].Childhood obesity has more than doubled in children and quadrupled in adolescents in the past 30 years [2]and has been known as a major risk factor for insulin resistance in children with metabolic syndrome [3]. The increasing incidenceof childhood obesity and the earlier onset of insulinresistance, hypertension, and dyslipidemia increased risk factors forcardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%